Evaluation of Vibratory Ball Mill Mixing as an Alternative to Wet Granulation in the Manufacturing of Sodium Naproxen Tablets with Dolomite-Based Formulations - Mateusz Przywara; Klaudia Jękot; Wiktoria Jednacz (Applied Sciences, 2025)
The development of robust and scalable tablet manufacturing methods remains a key objective in pharmaceutical technology, especially when dealing with active pharmaceutical ingredients (APIs) and excipients that exhibit suboptimal processing properties. This study evaluated two alternative manufacturing strategies for tablets containing sodium naproxen (20%, API), dolomite (65%, sustainable mineral filler), cellulose (7%), polyvinylpyrrolidone (5%, binder), and magnesium stearate (3%, lubricant). The direct compression method used a vibrating ball mill (SPEX SamplePrep 8000M), while the indirect method employed wet granulation using a pan granulator at different inclination angles. Physical properties of raw materials and granules were assessed, and final tablets were evaluated for mass, thickness, mechanical resistance, abrasiveness, and API content uniformity. Direct compression using vibratory mixing for 5–10 min (DT2, DT3) resulted in average tablet masses close to the target (0.260 g) and improved reproducibility compared to a reference V-type blender. Wet granulation produced tablets with the lowest abrasiveness (<1.0%) and minimal variability in dimensions and API content. The best uniformity (SD < 0.5%) was observed in batch IT2. Overall, vibratory mixing proved capable of achieving tablet quality comparable to that of wet granulation, while requiring fewer processing steps. This highlights its potential as an efficient and scalable alternative in solid dosage manufacturing.